2009
DOI: 10.1142/s0218271809015990
|View full text |Cite
|
Sign up to set email alerts
|

Can We See Naked Singularities?

Abstract: We study singularities which can form in a spherically symmetric gravitational collapse of a general matter field obeying weak energy condition. We show that no energy can reach an outside observer from a null naked singularity. That means they will not be a serious threat to the Cosmic Censorship Conjecture (CCC). For the timelike naked singularities, where only the central shell gets singular, the redshift is always finite and they can in principle, carry energy to a faraway observer. Hence for proving or di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 33 publications
(47 reference statements)
1
6
0
Order By: Relevance
“…Hence for proving or disproving CCC the study of timelike naked singularities is more important. The results of [45] were very general and independent of the initial data and the form of the matter.…”
Section: Spatial-temporal Vacuum Solutionsmentioning
confidence: 73%
See 1 more Smart Citation
“…Hence for proving or disproving CCC the study of timelike naked singularities is more important. The results of [45] were very general and independent of the initial data and the form of the matter.…”
Section: Spatial-temporal Vacuum Solutionsmentioning
confidence: 73%
“…Deshingkar [45] studied singularities which can form in a spherically symmetric gravitational collapse of a general matter field obeying the weak energy condition. He showed that no energy can reach an outside observer from a null naked singularity.…”
Section: Spatial-temporal Vacuum Solutionsmentioning
confidence: 99%
“…This means that, in principle such a singularity can be observed and they can be more problematic. However, as such we expect them to be very rare [37].…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, it is important to find out whether a naked singularity can affect the physics outside it, i.e., whether a nonsingular observer can distinguish it observationally. With this in mind we studied the spherically symmetric dust collapse model [37] and calculated the redshift and luminosity of light rays coming out of the singularity. Subsequently, we also studied extremely wide class of (any type II matter) spherically symmetric collapse models for the same purpose.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation